The Influence of the Dominant Leg in Body Asymmetries in Children and Adolescent Male Soccer Players - Eleni Theodorou; Theodoros B. Grivas; Marios Hadjicharalambous (MDPI AG, 2024)
The current study aimed to examine (a) whether the dominant leg (DL) was associated with the contralateral side of functional scoliosis and (b) if any of the postural asymmetries' evaluation variables may be a reliable predictor of the functional scoliosis development in young male soccer players. Six hundred-nine (n = 609) male soccer players (age: 10.8 ± 2.7 years; height: 147 ± 17 cm; weight: 43.4 ± 14.6 kg; DL: Right 81.6%, Left 14%, Both 4.4%) participated in this study. The spinal asymmetries evaluation included thoracic kyphosis, lumbar lordosis, truncal rotation, shoulders alignment from posterior view, anterior and posterior pelvic tilt, anterior superior iliac spine (ASIS), hamstring tightness, and lower extremities discrepancy. A significant association was observed between the DL and the truncal rotation side: χ2(4) = 30.84, p = 0.001, V = 0.16. Participants with longer left legs were likelier to present a spinal asymmetry (OR = 1.18). The participants with higher left shoulders were 2.13 times more likely to have spinal asymmetry than the participants with normal shoulders level. Participants with left ASIS higher were 3.08 times more likely to present asymmetry than those with normally aligned ASIS levels. There was also a significant association between the DL and the side of truncal rotation: χ2(2) = 13.30, p = 0.001, V = 0.449. Logistic regression analysis for the functional scoliotic group and truncal rotation side demonstrated that the taller participants and participants with shorter right legs were more likely to have asymmetry on the left side (OR = 1.29, OR = 0.32). Participants with greater right hamstring stiffness were likelier to have a truncal rotation on the right side (OR = 0.93). Participants with higher left shoulders were 0.20 times less likely to have a truncal rotation on the left side than the participants with normal shoulders level. In conclusion, leg dominance in children and in youth soccer players may be a factor causing truncal rotation on the contralateral side. Additional causes, such as leg length discrepancy and pelvic tilt, may progressively lead to functional scoliosis.